2022
DOI: 10.3390/nu14204264
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative and Energy Metabolism-Improving Effects of Maca Polysaccharide on Cyclophosphamide-Induced Hepatotoxicity Mice via Metabolomic Analysis and Keap1-Nrf2 Pathway

Abstract: Lepidium meyenii Walp. (Maca), as a natural food supplement, has strong antioxidant and energy metabolism-improving characteristics, and Maca polysaccharide (MP) is its effective component. MP has been shown to mitigate liver damage in previous research, and Cyclophosphamide (CYP)-induced hepatotoxicity is also a major concern in clinical practice. We investigated the possible cytoprotective effect of MP on CYP-induced liver injury, and explored its underlying mechanism by analyzing the resulting liver metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Furthermore, as mentioned earlier, BM intake has a positive effect on anti-oxidants, which can improve the 20 m-shuttle run for elite handball athletes. Maca supplements also play a protective role in cyclophosphamide-induced hepatotoxicity, where the Keap1-Nrf2 signaling pathway is regulated to improve oxidative stress, energy metabolism, and restore mitochondrial respiration to prevent liver damage (29). Therefore, for athletes with high-intensity training and competition, including handball, BM intake can have a positive effect on improving their performance by enhancing their cardiopulmonary endurance.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as mentioned earlier, BM intake has a positive effect on anti-oxidants, which can improve the 20 m-shuttle run for elite handball athletes. Maca supplements also play a protective role in cyclophosphamide-induced hepatotoxicity, where the Keap1-Nrf2 signaling pathway is regulated to improve oxidative stress, energy metabolism, and restore mitochondrial respiration to prevent liver damage (29). Therefore, for athletes with high-intensity training and competition, including handball, BM intake can have a positive effect on improving their performance by enhancing their cardiopulmonary endurance.…”
Section: Discussionmentioning
confidence: 99%
“…The affected lipids included LPC 18:3 and 12-HEPE, consistent with reports that CTX led to a decrease in polyunsaturated lysophosphatidylcholines and an increase in oxidized fatty acids. 37,38 Compared with separate extraction, the biomolecules recognized in simultaneous extraction could directly or indirectly establish relationships, reinforcing the idea of correlativity among these biomolecules. Additionally, more amino acids and transfer proteins (Cars, Gars, Qars, Rars, Fars2, Lars, and Acsf3) were identified in the simultaneous extraction, emphasizing the alteration in amino-acid-related metabolism in CTX-induced hepatic damage.…”
Section: Comparison Of Multiomics Correlation Networkmentioning
confidence: 90%
“…The intervention of electron transport chain on energy metabolism is inevitable on account of their close relations. Therefore, the de ciency in electron transport chain are capable of worsening ATP synthesis to a great extent [122]. Tong et al measured the activity of complex I and ATP production in two types of colorectal cancer cells after treated with certain concentration of aloe polysaccharide, and the result showed that the activity and intracellular ATP consistently declined, which indicated the treatment account for the inhibition of energy production [15].…”
Section: Electron Transport Chain (Etc) Complex Activity and Atp Prod...mentioning
confidence: 99%
“…Similar to the previous dimensions for the illustration on the protective effects, polysaccharides also possess certain functions on maintain or increase the activity of electron transport chains, thus disrupt mitochondrial dysfunction. Notably, Fei et al reported the expression of F 0 F 1 -ATPase, which is also known as complex enzyme V located on the mitochondrial membrane, was signi cantly enhanced by the addition of a natural Maca polysaccharide, and thereby reducing hepatotoxicity induced by cyclophosphamide due to better energy metabolism [122]. In another research, the signi cant nding was that a polysaccharide from G. lucidum could recover the reduction in the activity of complex I in ETC resulting from ageing, and therefore enhancing the electron ow from NADH 2 to O 2 [121].…”
Section: Electron Transport Chain (Etc) Complex Activity and Atp Prod...mentioning
confidence: 99%
See 1 more Smart Citation